Urgensi Penataan Ulang Mekanisme Pengisian Jabatan Penjabat Kepala Daerah Perspektif Demokrasi Konstitusional - Mazdan Maftukha Assyayuti (Lex Renaissance, 2022)
The mechanism for filling the post of interim Chief of Region in the pre-election 2024 leaves a problem with the future of democracy and constitutionalism. This study aims to answer the urgency of rearranging the mechanism for filling the positions of Chiefs of Region from the constitutional democracy. This research method uses normative/doctrinal research using a statutory and conceptual approach. The results of this study conclude: that there is an urgency to rearrange the filling of the position of the acting Chief of Region on the grounds that a) the central government has taken the constitutional rights of the people in the regions by appointing an official; b) There has been a shift in regional autonomy in the implementation of general elections, in this case the Minister of Home Affairs does not authoritatively consider the input of the governor in filling the temporary position of the acting Chief of Region. With such urgency, it should be the regional secretary who must fill the vacancy in the pre-election position in 2024.Key Words: Rearrangement; acting chief of region; constitutional democracy AbstrakMekanisme pengisian jabatan kepala daerah sementara pra-pemilu tahun 2024 menyisakan problematika terhadap masa depan demokrasi dan konstitusionalisme. Penelitian ini bertujuan menjawab urgensi penataan ulang mekanisme pengisian jabatan penjabat kepala daerah ditinjau dari demokrasi konstitusional. Metode penelitian ini menggunakan jenis penelitian normatif/doktrinal dengan menggunakan pendekatan perundang-undangan dan konseptual. Hasil penelitian ini menyimpulkan: bahwa terdapat urgensi penataan ulang pengisian jabatan penjabat kepala daerah dengan alasan a) Pemerintah pusat telah mengambil hak konstitusional masyarakat di daerah dengan mengangkat penjabat; b) Telah terjadi pergeseran otonomi daerah dalam penyelenggaraan pemilihan umum, dalam hal ini menteri dalam negeri secara otoritatif tidak mempertimbangkan masukan gubernur dalam pengisian jabatan sementara penjabat kepala daerah. Dengan urgensi demikian maka seharusnya sekretaris daerah yang harus mengisi kekosongan jabatan pra-pemilu tahun 2024. Kata-kata Kunci: Penataan ulang; penjabat kepala daerah sementara; demokrasi konstitusional